2017
DOI: 10.1186/s13567-016-0408-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diversity of Mycoplasma hyopneumoniae strains on lung lesions in slaughter pigs

Abstract: The importance of diversity of Mycoplasma hyopneumoniae (M. hyopneumoniae) strains is not yet fully known. This study investigated the genetic diversity of M. hyopneumoniae strains in ten pig herds, and assessed associations between the presence of different strains of M. hyopneumoniae and lung lesions at slaughter. Within each herd, three batches of slaughter pigs were investigated. At slaughter, from each batch, 20 post mortem bronchoalveolar lavage fluid samples were collected for multiple locus variable-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Information on the impact of strain variability may exert on lung lesions severity and clinical signs onset and duration is still not well defined. Whereas it has been reported that co‐infection with more than one strain resulted in more severe lesions (Michiels et al., ; Villarreal et al., ), such potentiation was not observed in others (Charlebois et al., ). To date, the lack of a known virulence marker together with the coexistence of different strains at individual and farm levels (Nathues, Grosse Beilage, Kreienbrock, Rosengarten, & Spergser, ; Pantoja, Pettit, Dos Santos, Tubbs, & Pieters, ; Vranckx, Maes, Del Pozo Sacristán, Pasmans, & Haesebrouck, ; Vranckx et al., ), prevent knowing the impact of a particular strain on the severity of clinical signs and lung lesions.…”
Section: Clinical Signs and Lesionsmentioning
confidence: 88%
See 1 more Smart Citation
“…Information on the impact of strain variability may exert on lung lesions severity and clinical signs onset and duration is still not well defined. Whereas it has been reported that co‐infection with more than one strain resulted in more severe lesions (Michiels et al., ; Villarreal et al., ), such potentiation was not observed in others (Charlebois et al., ). To date, the lack of a known virulence marker together with the coexistence of different strains at individual and farm levels (Nathues, Grosse Beilage, Kreienbrock, Rosengarten, & Spergser, ; Pantoja, Pettit, Dos Santos, Tubbs, & Pieters, ; Vranckx, Maes, Del Pozo Sacristán, Pasmans, & Haesebrouck, ; Vranckx et al., ), prevent knowing the impact of a particular strain on the severity of clinical signs and lung lesions.…”
Section: Clinical Signs and Lesionsmentioning
confidence: 88%
“…The use of M. hyopneumoniae molecular characterization has aided outbreak and area spread investigations, by tracking specific strains. In addition, it has enabled research directed at understanding pathogen variability and its relationship with disease presentation (Michiels et al., ). However, current tools for M. hyopneumoniae characterization are based on the sole evaluation of similarities in specific loci and do not indicate strain virulence and/or antigenicity.…”
Section: Epidemiologymentioning
confidence: 99%
“…Several M. hyopneumoniae strains can be detected in a herd and even in one individual pig from bronchoalveolar lavage fluid or lung tissue (Michiels et al, ; Nathues, Grosse Beilage, Kreienbrock, Rosengarten, & Spergser, ; Dos Santos et al, ; Vranckx et al, ). Although some studies point in the direction that co‐infection with more than one strain in a pig or batch of pigs might result in more severe lung lesions (Michiels et al, ; Villarreal et al, ; Vranckx et al, ), other studies did not detect such a relationship (Charlebois et al, ). Michiels et al () investigated the genetic diversity of M. hyopneumoniae strains in different successive batches of 10 pig herds using Multiple‐Locus Variable number tandem repeat Analysis (MLVA).…”
Section: Mycoplasma Hyopneumoniae Variabilitymentioning
confidence: 99%
“…Although some studies point in the direction that co‐infection with more than one strain in a pig or batch of pigs might result in more severe lung lesions (Michiels et al, ; Villarreal et al, ; Vranckx et al, ), other studies did not detect such a relationship (Charlebois et al, ). Michiels et al () investigated the genetic diversity of M. hyopneumoniae strains in different successive batches of 10 pig herds using Multiple‐Locus Variable number tandem repeat Analysis (MLVA). Multivariable analyses accounting for the potential effect of risk factors for respiratory disease were performed to assess associations between the number of different Variable Number Tandem Repeats (VNTR) variants per batch and lung lesions as outcome variables.…”
Section: Mycoplasma Hyopneumoniae Variabilitymentioning
confidence: 99%
See 1 more Smart Citation